Composition and application of high-performance low-density cement paste system suitable for wide temperature range

By adding modified hollow glass microbeads, hydration process regulators and crystal form transition inhibitors to low-density cement slurry, combined with water loss-reducing agents and other supporting agents, the problems of slow development of cement slurry strength and long-term decline under a wide temperature range are solved, and early strength improvement and long-term stability of high-strength low-density cement slurry system are achieved.

CN119822694APending Publication Date: 2025-04-15CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510015649.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Under a wide temperature range, the strength of the top cement slurry develops slowly and the long-term strength declines significantly, making it difficult to meet the cementing needs of deep and ultra-deep wells.

Method used

By adding modified hollow glass microbeads, hydration process regulators and crystal form transition inhibitors to low-density cement slurry, the type of hydration product and its microstructure of cement stones is regulated, the intensity decline phenomenon is reduced, and the early intensity development rate is improved through supporting water loss reduction agents, retarders, drag reducing agents and defoaming agents.

Benefits of technology

A high-strength low-density cement slurry system that can meet the cementing requirements within a wide temperature range of 30 to 150℃ has been formed. The early strength develops rapidly, the long-term strength stability is high, and the degree of strength decline is low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the field of well cementation operation in petroleum engineering, and discloses a high-performance low-density cement paste system suitable for a wide temperature range and application. The cement paste system comprises the following components in parts by weight: 100 parts of oil well G-grade cement, 20-28 parts of modified hollow glass beads, 3-15 parts of a hydration process regulator, 5-10 parts of a crystal form transition inhibitor, 1-2 parts of a drag reducer, 3-6 parts of a fluid loss agent, 3-4 parts of a retarder, 0.2-1.0 part of a defoaming agent and 44-54 parts of water, according to the high-performance low-density cement paste system suitable for the wide temperature range condition, the cement paste fluidity is good, the thickening time is adjustable, through matched use of the retarder and the fluid loss agent, the problem that the strength development of the top cement paste is slow under the wide temperature range condition is solved, the long-term strength development is stable, the internal microstructure of set cement is compact, and the performance is good. And engineering requirements can be met, and well cementation engineering safety and engineering quality are effectively guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil and gas field development, and is particularly suitable for oil and gas resource development operation environments where the temperature difference between the top and bottom of a long cementing section is large, the formation is prone to compression and leakage, and high requirements are placed on the density, early low-temperature strength and long-term strength of cement in oil and gas wells. Background Art

[0002] At present, nearly 60% of the world's energy supply comes from oil and natural gas. With the continuous reduction of conventional oil and gas reserves and the increasing difficulty of mining, my country's dependence on foreign oil and gas resources is increasing, which seriously endangers national energy security. In order to increase the output of oil and gas resources, future oil and gas exploration and development will gradually develop towards deep wells, ultra-deep wells, and complex formations. China accounts for a large proportion of the global deep and ultra-deep oil and gas discoveries, and major strategic breakthroughs in recent years have been in deep and ultra-deep formations. Only by reducing the density of cement slurry and preparing low-density cement slurry can we meet the deep low-pressure formation cementing of deep and ultra-deep wells. Internationally, formations of 3500m to 4500m are considered deep formations, and formations greater than 4500m are considered ultra-deep formations.

[0003] Cementing is an important operation to ensure complete isolation of interlayers during well construction. The development of deep and ultra-deep wells has also brought huge requirements and challenges to cementing operations. During cementing operations, the physical and chemical structures of cementing cement and cement slurry systems will change. Deep and ultra-deep well cementing has problems such as long cementing sections, cross-temperature zone cementing, and small annular gaps. The continuous increase in low-pressure formations and weak formations also means that the use of conventional density cement slurry may cause formation pressure leakage. Therefore, low-density cement slurry systems are often used as an effective means to solve the problems of cementing in long cementing sections, wide temperature ranges, and low-pressure leaky layers.

[0004] As exploration and development continue to deepen, the number of cementing operations with long sealing sections continues to increase. The casing sealing section is long, and the temperature difference between the upper and lower parts of the cement slurry is large, which leads to slow development of the strength of the top cement, and does not meet the requirements of short waiting time. The cement slurry at the top of the wellbore is prone to problems such as low strength and slow development, which makes cementing safety unguaranteed.

[0005] During the wellbore cement curing process, the mechanical strength of cement will be significantly reduced due to the limited degree of crystallization of hydration products generated by cement hydration, crystal dehydration, structural transformation, and increased porosity. This phenomenon is called "strength decay", that is, the compressive strength of cement decreases with the extension of curing time. In cementing operations, the strength decay of cement is a huge challenge to cementing safety. And the strength decay phenomenon exists not only under high-temperature curing conditions, but also under all temperature conditions.

[0006] In cementing projects, "temperature difference" is defined as the difference between the bottom hole circulating temperature and the static temperature at the top of the cement. When this temperature difference is higher than 40°C, it can be considered a large temperature difference. When the bottom hole temperature is lower than 110°C, it is a low temperature and large temperature difference condition. The temperature range is wide, and it has more stringent requirements on the system admixtures and comprehensive performance.

[0007] Cementing with a long sealing section and a wide temperature range requires that the cement slurry must not only ensure safe pumping under high temperature conditions at the bottom of the well, but also meet the requirements of high early strength and fast strength development of the top cement stone. Since the on-site cement slurry system is designed based on the bottom of the well temperature, the strength of the upper part of the cement is formed slowly, and it may not solidify for a long time. It transmits liquid column pressure without forming cementing strength, which is very easy to form oil, gas and water channeling grooves, which not only increases the drilling cycle, but also may affect the cementing quality and the long-term development of oil and gas fields.

[0008] A Chinese patent with publication number CN112094091B discloses a low-density, low-thermal conductivity cementing slurry system with large temperature difference suitable for long sealing sections. This technology mixes low-thermal conductivity materials into low-density cement slurry. The cement stone has a certain compressive resistance after 48 hours, but the early strength of the system still has room for improvement.

[0009] The Chinese patent with publication number CN116023071A discloses an ultra-low density cement slurry system and an ultra-low density cement slurry additive. The invention patent discloses a system with a temperature resistance of 120-150°C and a density of 1.15-1.25 g / cm 3 The ultra-low density cement slurry system uses ultra-fine microspheres and ultra-fine silica powder to mix to prepare a low-density lightener. It is cured at 150°C for 48 hours and has a strength of about 7MPa. However, its temperature resistance range is narrow and cannot meet the cementing requirements under a wide temperature range.

[0010] The Chinese patent with publication number CN117025188A discloses a low thermal conductivity admixture for deepwater shallow cementing, its preparation method and application, which achieves the requirements of high strength and low thermal conductivity by using hollow sodium aluminosilicate microspheres with hollow glass microspheres wrapped on the surface of resin. However, the microspheres wrapped in resin often have a high density and cannot meet the requirements of low-density cementing.

[0011] The Chinese patent with publication number CN118388161A discloses a method for modifying fly ash floating beads and a corresponding method for preparing high-strength cement slurry and its application. The fly ash floating beads are etched by a corrosive solution to reveal their internal loose structure, so that the amount of water in the cement hydration reaction is increased in the early stage of hydration, and the cracks caused by the self-shrinkage of the cement are reduced. However, the corrosion of the fly ash floating beads will cause their strength to decrease and the breakage rate to increase, making their low-density reduction function ineffective.

[0012] The Chinese patent with publication number CN119100704A discloses a high-temperature, large temperature difference, early-strength, low-density cementing slurry and its preparation method. By adding high-temperature strength stabilizers, early-strength agents and other admixtures to the cement slurry, the problems of poor rheological properties, excessive water loss, poor high-temperature stability, and slow strength development of the large temperature difference, low-density cement slurry are solved. However, its temperature resistance range is narrow, and it fails to ensure that the long-term strength development of the cement paste meets the cementing strength requirements.

[0013] In summary, the low-density cement slurry systems represented by existing patents and articles are mainly based on low-density cement slurry formulas for different needs, such as high solid content, low thermal conductivity, etc., and in-depth research is still needed in terms of early strength development and long-term strength evolution.

[0014] Therefore, it is urgent to develop a high-strength, low-density cement slurry system suitable for a wide temperature range. Through the synergistic effect of various cement regulating materials and admixtures, the objective engineering needs of rapid early strength improvement and stable long-term strength development can be achieved to ensure the safety of cementing construction and the overall cementing quality. Summary of the invention

[0015] The present invention aims at the problems of slow strength development of top cement slurry and significant long-term strength decline under wide temperature range cementing conditions. Based on the research on the hydration process and hydration products of conventional low-density cement slurry, the present invention adds three key additives, namely, modified hollow glass microspheres, hydration process regulator and crystal transformation inhibitor, to low-density cement slurry. Under the premise of ensuring the low density of cement slurry, the type of hydration product and its microstructure of cement stone are regulated, thereby reducing the significant decline of mechanical strength of cement stone after long-term maintenance. The early strength development rate of cement stone is improved through the combined effects of fluid loss reducer, retarder, drag reducer and defoamer. Finally, a high-strength low-density cement slurry system that can meet the cementing requirements under wide temperature range of 30 to 150°C is formed.

[0016] In order to improve the density and early strength of low-density cement paste, this patent adds modified hollow glass beads to the low-density cement slurry for cementing. Compared with conventional hollow glass beads, highly active nano-silica is attached to the surface of hollow glass beads through the fluidized bed process. On the premise of improving the bonding density between the beads and the cement matrix, the nano-silica participates in the volcanic ash reaction, promotes the hydration process and further improves the early strength and strength development rate of the cement paste.

[0017] In order to improve the long-term strength development of low-density cement paste, this patent adds a hydration process regulator to the low-density cement slurry for cementing. The hydration process regulator participates in the secondary hydration reaction in the later stage of strength development, further consumes the loose lamellar deposition product Ca(OH)2 in the cement, and converts it into a stable dense hydration product, thereby extending the duration of the mechanical strength rising period of the cement paste and delaying the time point when the strength decline occurs.

[0018] In order to improve the structural coarsening of calcium silicate hydrate in low-density cement paste, this patent adds a crystal transformation inhibitor to the low-density cement slurry for cementing. It improves the overall calcium-silicon ratio inside the cement paste, inhibits the transformation of high-calcium-silicon ratio dense hydration products (hydroxycalcium silicate, heavy calcium silicate) to low-calcium-silicon ratio hydration products (calcium silicate, tobermorite and white calcium zeolite), and reduces the strength decline of cement paste after long-term hydration.

[0019] In order to achieve the object of the present invention, the technical solution of the present invention is as follows:

[0020] A high-performance low-density cement slurry system suitable for a wide temperature range, characterized in that it comprises the following components by weight: 100 parts of oil well G-grade cement, 20-28 parts of modified hollow glass microspheres, 3-15 parts of hydration process regulator, 5-10 parts of crystal transformation inhibitor, 1-2 parts of drag reducer, 3-6 parts of fluid loss reducer, 3-4 parts of retarder, 0.2-1.0 parts of defoamer and 44-54 parts of water;

[0021] The high-performance, low-density cement slurry system suitable for a wide temperature range is characterized in that the modified hollow glass microspheres are hollow glass microspheres after nano-silicon dioxide deposition. The specific preparation process is as follows: under the condition of a stirring speed of 300-550r / min, add 20 parts of ethyl orthosilicate and 20 parts of anhydrous ethanol to 60 parts of deionized water, and then use a hydrochloric acid solution with a mass fraction of 25-37% to adjust the pH value of the solution to pH = 2.5, continue stirring until the solution is clear, and then use a 20-25% ammonia solution to adjust to pH = 7.5 to obtain a silica prefabricated liquid. Then, place a number of hollow glass microspheres in a fluidized bed, set the internal temperature of the fluidized bed to 70-80°C, and set the gas flow rate in the fluidized bed to 40-60m 3 / h, so that the hollow glass microspheres float evenly in the middle of the fluidized bed to form an ideal fluidized state. Subsequently, a mist nozzle is used to gradually and evenly spray the silica prefabricated liquid from the bottom of the fluidized bed. The silica prefabricated liquid rises and reaches the hollow glass microspheres, adheres to the surface of the microspheres, and then decomposes under high temperature conditions, so that the generated nano-silicon dioxide forms a uniformly covered silica film. After that, due to the increase in weight of the microspheres, the hollow glass microspheres will settle to the bottom of the fluidized bed with the airflow. Finally, the settled hollow glass microspheres are cleaned and dried to complete the preparation of the modified hollow glass microspheres. Preferably, the density of the modified hollow glass microspheres is between 0.68-0.72g / cm 3 , particle size D90≤100μm.

[0022] The high-performance low-density cement slurry system suitable for a wide temperature range is characterized in that the hydration process regulator is obtained by grinding and calcining coal gangue, bauxite, montmorillonite, and zirconium oxide and mixing them uniformly according to 15-25:20-35:25-30:25-30 parts by weight. The specific preparation process is as follows: coal gangue, bauxite, montmorillonite, and zirconium oxide are preliminarily crushed to coarse particles of 50-100 mesh size, and then the coarse particles are placed in a drying box at 120°C for 24 hours. After drying, they are placed in a ball mill for ball milling, and the ball milling time is a total of 120 minutes. After the ball milling is completed, the coal gangue, bauxite, montmorillonite and zirconia are placed in a muffle furnace for high-temperature calcination. The calcination temperature is set to 800°C. The mixed material is put into an uncovered ash dish with a small spoon, and the ash dish is placed on an iron frame and placed in a muffle furnace for constant temperature 800°C calcination; after calcination for 2 hours, it is taken out and naturally cooled. When it is cooled to 100°C, it is placed in a vacuum dryer and continued to cool to room temperature. After that, it is screened with a 200-mesh sieve to obtain a hydration process regulator. It promotes the secondary hydration reaction in the middle and late stages of the reaction, prolongs the time interval of the cement stone strength increase period, and thus prolongs the time node of the strength decline. Among them, the particle size of coal gangue is between 40 and 50μm, the particle size of bauxite is between 20 and 50μm, the particle size of montmorillonite is between 35 and 75μm, and the particle size of zirconia is between 30 and 65μm.

[0023] The high-performance, low-density cement slurry system suitable for a wide temperature range is characterized in that the crystal transformation inhibitor is a high-calcium mineral material, and its high calcium-silicon ratio can further improve the calcium-silicon ratio of the cement slurry after being added to the cement slurry, and by inhibiting the coarsening structural transformation of hydrated calcium silicate in the cement slurry, reduce the generation of loose structure low calcium-silicon ratio products. The crystal transformation inhibitor is obtained by mixing calcium aluminate, hydrocalumite and spodumene tailings powder in a weight ratio of 20-30:30-45:20-40. The specific preparation process is as follows: the above-mentioned calcium aluminate, hydrocalumite and spodumene tailings are preliminarily crushed to coarse particles of 50-100 mesh size, and then the coarse particles are placed in a drying box and dried at 120°C for 24 hours. After drying, they are placed in a ball mill for ball milling, and the ball milling time is a total of 120 minutes. To obtain uniform and fine mineral powders, they are screened separately using a 200-mesh sieve, and the screened minerals are mixed to obtain a crystal transformation inhibitor. Among them, the particle size of calcium aluminate is between 30 and 75 μm, the particle size of hydrocalumite is between 40 and 75 μm, and the particle size of spodumene tailings powder is between 45 and 75 μm.

[0024] The high-performance low-density cement slurry system suitable for a wide temperature range is characterized in that the fluid loss reducer is obtained by free radical copolymerization of N,N-dimethylacrylamide (NNDMA), 2-acrylamide-2-methylpropanesulfonic acid (AMPS), sodium styrene sulfonate (SSS) and acrylic acid (AA) in a weight ratio of 27-40:24-38:10-16:18-27 in pure water at 50-55°C through a sodium bisulfite-ammonium persulfate initiator system, wherein the reaction pH is 5.5-6.5 and the reaction time is 240-300 minutes.

[0025] A high-performance low-density cement slurry system suitable for a wide temperature range, characterized in that the retarder is itaconic acid (IA), 2-acrylamido-2-methylpropanesulfonic acid (AMPS), N,N-dimethylacrylamide (NNDMA) and a long-chain alkyl quaternary ammonium salt-containing hydrophobic monomer dissolved in deionized water in a weight ratio of 6.57-10.51:8.36-9.2:1:0.8-1.21, and a persulfate-sodium bisulfite initiator is added to undergo an oxidation reaction to obtain the retarder, wherein the reaction pH is 4-6 and the reaction time is 10-12 hours.

[0026] The high-performance low-density cement slurry system suitable for a wide temperature range is characterized in that the drag reducer is one of a sulfonated aldehyde ketone condensation drag reducer, a naphthalene sulfonate drag reducer, and a polycarboxylic acid drag reducer, or a mixture thereof.

[0027] The high-performance, low-density cement slurry system suitable for a wide temperature range is characterized in that the defoamer is one or a mixture of a phosphate defoamer, an organosiloxane defoamer, an organic polyether defoamer, and an organosilicon ether defoamer.

[0028] The high-performance low-density cement slurry system suitable for a wide temperature range is characterized in that the oil well cement is G-grade oil well cement or H-grade oil well cement.

[0029] The high-performance low-density cement slurry system suitable for a wide temperature range is characterized in that the water is fresh water or low-mineralization water.

[0030] According to the present invention, the high-performance low-density cement slurry system suitable for a wide temperature range can rapidly form early strength in the top low-temperature section according to relevant industry standards, and resist long-term strength decay under a wide temperature range of 30°C to 150°C. The types and amounts of four key additives can be optimized according to the on-site use environment and requirements, the amounts of fluid loss reducers, drag reducers, retarders, defoamers and other materials can be optimized, and the engineering properties of the cement slurry system such as water loss, rheological parameters, and thickening time can be optimized and adjusted to meet the on-site construction requirements of cementing.

[0031] According to the present invention, the high-performance low-density cement slurry system suitable for a wide temperature range comprises the following steps:

[0032] Weigh the raw materials according to the following weight proportions: 100 parts of oil well G grade cement, 20-28 parts of modified hollow glass microspheres, 3-15 parts of hydration process regulator, 5-10 parts of crystal transformation inhibitor, 1-2 parts of drag reducer, 3-6 parts of fluid loss reducer, 3-4 parts of retarder, 0.2-1.0 parts of defoamer and 44-54 parts of water;

[0033] At room temperature, the weighed G-grade cement, modified hollow glass microspheres, hydration process regulator, crystal transformation inhibitor, drag reducer, etc. are mixed and stirred evenly to obtain a solid mixture. Liquid components such as fluid loss reducer, retarder, defoamer, etc. are mixed with water to obtain a liquid mixture.

[0034] After the solid phase and liquid phase are mixed evenly after configuration, the liquid phase mixture is introduced into a high-speed rotating agitator. Within 15 seconds, solid materials such as oil well cement are continuously and evenly poured into the stirring slurry cup at a rotation speed of 4000 rpm to mix with the liquid phase. Then, the rotation speed is adjusted to 6000 rpm and stirred for 35 seconds to obtain the low-temperature, wide temperature range and low-density cement slurry system of this embodiment.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) The high-performance low-density cement slurry system suitable for a wide temperature range of the present invention has the characteristics of a wide temperature application range, rapid early strength development, high long-term strength stability, low strength decay, good rheology, stable slurry, low filtration loss, and adjustable thickening time. The density is 1.30-1.40g / cm 3 After curing for 90 days at 90℃, the compressive strength of cement paste is >27.3MPa.

[0037] (2) The high-performance low-density cement slurry system of the present invention is suitable for a wide temperature range. By adopting a fluidized bed process, a layer of nano-silicon dioxide is uniformly deposited on the surface of hollow glass microspheres. On the one hand, the hollow glass microspheres are used to reduce the density of the cement slurry system, reduce the risk of formation pressure leakage, and meet the formation sealing requirements. On the other hand, the nano-silicon dioxide deposited on the surface of the hollow glass microspheres participates in the cement hydration reaction, strengthens the bonding condition of the cement interface between the cement stone and the hollow glass microspheres, further improves the density of the cement stone, and reduces the cracking condition of the cement stone.

[0038] (3) The key additive materials required for the high-performance low-density cement slurry system suitable for a wide temperature range of the present invention are widely available and inexpensive, and can play the designed role within a relatively wide range of addition, which is convenient for construction operations; secondly, the fluidized bed technology has a perfect application environment and can meet the large-scale on-site construction dosage requirements.

[0039] (4) The high-performance low-density cement slurry system of the present invention is applicable to sealing sections in a wide temperature range and formations that are prone to compression and leakage, and can meet the early strength requirements of the top low-temperature cement slurry and the sealing mechanical strength requirements after long-term production of the oil well. DETAILED DESCRIPTION

[0040] The present invention is further described below by means of specific examples and comparative examples, but is not limited thereto.

[0041] Experimental method: According to the standard GB / T 19139-2012 "Test method for oil well cement", a high-performance low-density cement slurry system suitable for a wide temperature range was prepared, and according to the standard SY / T6544-2017 "Performance requirements for oil well cement slurries", the performance of a high-performance low-density cement slurry system suitable for a wide temperature range was tested.

[0042] The sources and properties of the raw materials used in the following examples and comparative examples are as follows:

[0043] Oil well cement: Use Grade G oil well cement produced by Jiahua Special Cement Co., Ltd.

[0044] Hollow glass microspheres: purchased from Zhengzhou Shenglait Hollow Microsphere New Material Co., Ltd., with a density between 0.58 and 0.62 g / cm 3 , particle size D90≤80μm, compressive strength≈82.76MPa, and floating rate greater than 92%.

[0045] Coal gangue, purchased from Henan Jinrun New Materials Co., Ltd., black-gray powder, about 200 mesh to 325 mesh.

[0046] Alumina stone, purchased from Shanxi Xi'an Yicheng New Materials Manufacturing Co., Ltd., off-white powder, density 3.45g / cm 3 , hardness 1~3.

[0047] Montmorillonite was purchased from Dongguan Ruiheng Mineral Products Co., Ltd., yellow powder, about 200 mesh.

[0048] Zirconia was purchased from Hangzhou Jikang New Materials Co., Ltd., with a ZrO2 content of >94.7%.

[0049] Calcium aluminate, purchased from Fenyangtang (Shanghai) Industrial Co., Ltd., about 200 mesh.

[0050] Hydrocalumite was purchased from Jining Fangyu Chemical Co., Ltd.

[0051] Spodumene tailings, purchased from Lingshou County Chuangbo Mineral Products Co., Ltd., hardness 6.5-7, density 3.03-3.22g / cm 3 .

[0052] Ethyl orthosilicate: purchased from Shandong Sike New Materials Co., Ltd., a colorless transparent liquid, melting point: -82.49°C, boiling point: 168°C, relative density: 0.934 g / cm 3 , flash point: 45℃, auto-ignition temperature: 222℃.

[0053] Drag reducer: HX-21L drag reducer for oil well cement produced by Chengdu OMEC Petroleum Technology Co., Ltd.

[0054] Defoamer: Chengdu OMEC Petroleum Technology Co., Ltd., defoamer DF-A for oil well cement.

[0055] Example 1

[0056] The present embodiment provides a high-performance, low-density cement slurry system suitable for a wide temperature range, which is composed of the following components: 100 parts of G-grade oil well cement, 26 parts of modified hollow glass microspheres, 5 parts of a hydration process regulator (coal gangue, bauxite, montmorillonite, and zirconium oxide are uniformly mixed at a weight ratio of 15:20:25:27), 5 parts of a crystal transformation inhibitor (calcium aluminate, hydrocalumite, and spodumene tailings are uniformly mixed at a weight ratio of 25:30:23), 1.5 parts of a drag reducer, 3.75 parts of a retarder, 6 parts of a fluid loss reducer, 2 parts of a defoamer, and 54 parts of water.

[0057] The preparation method of the high-performance low-density cement slurry system suitable for large temperature difference conditions in this embodiment comprises the following steps:

[0058] (1) According to the standards GB / T 19139-2012 "Test methods for oil well cement" and GB / T 33294-2016 "Test methods for deepwater oil well cement", G-grade cement, modified hollow glass microspheres, hydration process regulator, crystal transformation inhibitor, drag reducer, etc. are mixed and stirred uniformly to obtain a solid mixture. Liquid components such as fluid loss additive, retarder, defoamer, etc. are mixed with water to obtain a liquid mixture.

[0059] (2) After the solid phase and liquid phase are uniformly mixed, the liquid phase mixture is introduced into a high-speed rotating agitator. Within 15 seconds, solid materials such as oil well cement are continuously and uniformly poured into the stirring slurry cup at a speed of 4000 rpm to mix with the liquid phase. Then, the speed is adjusted to 6000 rpm and stirred for 35 seconds to obtain the low-temperature, large temperature difference and low-density cement slurry system of this embodiment.

[0060] (3) The cement slurry was placed in a high-temperature and high-pressure thickener and aged at 140°C and 60 MPa for 1 h to simulate the temperature rise conditions experienced by the cement slurry after entering the wellbore. After the aging process, the cement slurry was taken out and made into standard strength test blocks and cured at 75°C, 90°C, and 105°C and 21 MPa.

[0061] Example 2

[0062] The present embodiment provides a high-performance low-density cement slurry system suitable for a wide temperature range, which is composed of the following components: 100 parts of G-grade oil well cement, 26 parts of modified hollow glass microspheres, 10 parts of a hydration process regulator (coal gangue, bauxite, montmorillonite, and zirconium oxide are uniformly mixed at a weight ratio of 15:20:25:27), 5 parts of a crystal transformation inhibitor (calcium aluminate, hydrocalumite, and spodumene tailings are uniformly mixed at a weight ratio of 25:30:23), 1.5 parts of a drag reducer, 3.75 parts of a retarder, 6 parts of a fluid loss reducer, 2 parts of a defoamer, and 54 parts of water.

[0063] The high-performance low-density cement slurry system suitable for large temperature difference conditions in this embodiment is prepared by the same method as in Example 1.

[0064] Example 3

[0065] The present embodiment provides a high-performance, low-density cement slurry system suitable for a wide temperature range, which is composed of the following components: 100 parts of G-grade oil well cement, 26 parts of modified hollow glass microspheres, 15 parts of a hydration process regulator (coal gangue, bauxite, montmorillonite, and zirconium oxide are uniformly mixed at a weight ratio of 15:20:25:27), 5 parts of a crystal transformation inhibitor (calcium aluminate, hydrocalumite, and spodumene tailings are uniformly mixed at a weight ratio of 25:30:23), 1.5 parts of a drag reducer, 3.75 parts of a retarder, 6 parts of a fluid loss reducer, 2 parts of a defoamer, and 54 parts of water.

[0066] The high-performance low-density cement slurry system suitable for large temperature difference conditions in this embodiment is prepared by the same method as in Example 1.

[0067] Example 4

[0068] The present embodiment provides a high-performance, low-density cement slurry system suitable for a wide temperature range, which is composed of the following components: 100 parts of G-grade oil well cement, 26 parts of modified hollow glass microspheres, 5 parts of a hydration process regulator (coal gangue, bauxite, montmorillonite, and zirconium oxide are uniformly mixed at a weight ratio of 15:20:25:27), 10 parts of a crystal transformation inhibitor (calcium aluminate, hydrocalumite, and spodumene tailings are uniformly mixed at a weight ratio of 25:30:23), 1.5 parts of a drag reducer, 3.75 parts of a retarder, 6 parts of a fluid loss reducer, 2 parts of a defoamer, and 54 parts of water.

[0069] The large temperature difference and low density cement slurry system of this embodiment is prepared by the same method as that of Example 1.

[0070] Example 5

[0071] The present embodiment provides a high-performance, low-density cement slurry system suitable for a wide temperature range, which is composed of the following components: 100 parts of G-grade oil well cement, 26 parts of modified hollow glass microspheres, 10 parts of a hydration process regulator (coal gangue, bauxite, montmorillonite, and zirconium oxide are uniformly mixed at a weight ratio of 15:20:25:27), 10 parts of a crystal transformation inhibitor (calcium aluminate, hydrocalumite, and spodumene tailings are uniformly mixed at a weight ratio of 25:30:23), 1.5 parts of a drag reducer, 3.75 parts of a retarder, 6 parts of a fluid loss reducer, 2 parts of a defoamer, and 54 parts of water.

[0072] The high-performance low-density cement slurry system suitable for large temperature difference conditions in this embodiment is prepared by the same method as in Example 1.

[0073] Example 6

[0074] The present embodiment provides a high-performance, low-density cement slurry system suitable for a wide temperature range, which is composed of the following components: 100 parts of G-grade oil well cement, 26 parts of modified hollow glass microspheres, 15 parts of a hydration process regulator (coal gangue, bauxite, montmorillonite, and zirconium oxide are uniformly mixed at a weight ratio of 15:20:25:27), 10 parts of a crystal transformation inhibitor (calcium aluminate, hydrocalumite, and spodumene tailings are uniformly mixed at a weight ratio of 25:30:23), 1.5 parts of a drag reducer, 3.75 parts of a retarder, 6 parts of a fluid loss reducer, 2 parts of a defoamer, and 54 parts of water.

[0075] The large temperature difference and low density cement slurry system of this embodiment is prepared by the same method as that of Example 1.

[0076] Example 7

[0077] The present embodiment provides a high-performance, low-density cement slurry system suitable for a wide temperature range, which is composed of the following components: 100 parts of G-grade oil well cement, 26 parts of modified hollow glass microspheres, 5 parts of a hydration process regulator (coal gangue, bauxite, montmorillonite, and zirconium oxide are uniformly mixed at a weight ratio of 25:35:30:27), 10 parts of a crystal transformation inhibitor (calcium aluminate, hydrocalumite, and spodumene tailings are uniformly mixed at a weight ratio of 25:30:23), 1.5 parts of a drag reducer, 3.75 parts of a retarder, 6 parts of a fluid loss reducer, 2 parts of a defoamer, and 54 parts of water.

[0078] The high-performance low-density cement slurry system suitable for large temperature difference conditions in this embodiment is prepared by the same method as in Example 1.

[0079] Example 8

[0080] The present embodiment provides a high-performance, low-density cement slurry system suitable for a wide temperature range, which is composed of the following components: 100 parts of G-grade oil well cement, 26 parts of modified hollow glass microspheres, 10 parts of a hydration process regulator (coal gangue, bauxite, montmorillonite, and zirconium oxide are uniformly mixed at a weight ratio of 25:35:30:27), 10 parts of a crystal transformation inhibitor (calcium aluminate, hydrocalumite, and spodumene tailings are uniformly mixed at a weight ratio of 25:30:23), 1.5 parts of a drag reducer, 3.75 parts of a retarder, 6 parts of a fluid loss reducer, 2 parts of a defoamer, and 54 parts of water.

[0081] The high-performance low-density cement slurry system suitable for large temperature difference conditions in this embodiment is prepared by the same method as in Example 1.

[0082] Example 9

[0083] The present embodiment provides a high-performance, low-density cement slurry system suitable for a wide temperature range, which is composed of the following components: 100 parts of G-grade oil well cement, 26 parts of modified hollow glass microspheres, 15 parts of a hydration process regulator (coal gangue, bauxite, montmorillonite, and zirconium oxide are uniformly mixed at a weight ratio of 25:35:30:27), 10 parts of a crystal transformation inhibitor (calcium aluminate, hydrocalumite, and spodumene tailings are uniformly mixed at a weight ratio of 25:30:23), 1.5 parts of a drag reducer, 3.75 parts of a retarder, 6 parts of a fluid loss reducer, 2 parts of a defoamer, and 54 parts of water.

[0084] The large temperature difference and low density cement slurry system of this embodiment is prepared by the same method as that of Example 1.

[0085] Comparative Example 1

[0086] This comparative example is compared with Example 1, and the following raw materials are added in parts by weight: 100 parts of G-grade oil well cement, 26 parts of hollow glass microspheres, 3.75 parts of retarder, 6 parts of fluid loss additive, 2 parts of defoamer and 54 parts of water.

[0087] The preparation method is the same as that of Example 1

[0088] Comparative Example 2

[0089] This comparative example is compared with Example 1, and the following raw materials are added in parts by weight: 100 parts of G-grade oil well cement, 26 parts of hollow glass microspheres, 5 parts of hydration process regulator, 3.75 parts of retarder, 6 parts of fluid loss reducer, 2 parts of defoamer and 54 parts of water.

[0090] The preparation method is the same as that of Example 1

[0091] Comparative Example 3

[0092] This comparative example is compared with Example 1, and the following raw materials are added in parts by weight: 100 parts of G-grade oil well cement, 26 parts of hollow glass microspheres, 5 parts of hydration process regulator, 5 parts of crystal transformation inhibitor, 3.75 parts of retarder, 6 parts of fluid loss reducer, 2 parts of defoamer and 54 parts of water.

[0093] Comparative Example 4

[0094] This comparative example is compared with Example 1, and the following raw materials are added in parts by weight: 100 parts of G-grade oil well cement, 26 parts of hollow glass microspheres, 5 parts of hydration process regulator, 5 parts of crystal transformation inhibitor, 6 parts of fluid loss reducer, 2 parts of defoamer and 54 parts of water.

[0095] The preparation method is the same as that of Example 1

[0096] Experimental Example 1: Slurry Performance Test of Large Temperature Difference and Low Density Cement Slurry System

[0097] The high-performance low-density cement slurry system suitable for large temperature difference conditions of Examples 1 to 9 and Comparative Examples 1 to 4 were used as test objects. According to the standard GB / T 19139-2012 "Test methods for oil well cement", G-grade cement, modified hollow glass microspheres, hydration process regulator, crystal transformation inhibitor, drag reducer, etc. were mixed and stirred uniformly to obtain a solid mixture. Liquid components such as fluid loss reducer, retarder, defoamer and water were mixed to obtain a liquid mixture. The working fluid performance was measured according to SY / T 6544-2017 "Oil well cement slurry performance requirements", and the test results are shown in Table 1.

[0098] Table 1 Slurry properties of high-performance low-density cement slurry system suitable for large temperature difference conditions

[0099]

[0100]

[0101] According to Table 1, the high-performance low-density cement slurry system suitable for a wide temperature range prepared in Examples 1 to 9 of the present invention has a lower density and better water loss stability, and the thickening time can also meet the relevant requirements of on-site cementing construction.

[0102] Experimental Example 2: Compressive Strength Test of Different Cementing Material Systems

[0103] The cementing material systems of Examples 1 to 9 and Comparative Examples 1 to 4 were used as test objects. The solid components and liquid water components in the cementing materials used for slurry preparation were first weighed and mixed, and then the slurry was prepared according to the standard GB / T 19139-2012 "Test methods for oil well cement". The cement slurry was first placed in a high temperature and high pressure thickener and aged for 1 hour at 140°C and 60 MPa to simulate the temperature rise conditions experienced by the cement slurry after entering the wellbore. Then, the compressive strength was measured after curing for 7 days, 14 days, 30 days, 60 days, and 90 days at 21 MPa. The experimental results are shown in Table 2.

[0104] Table 2 Compressive strength properties of different cementing material systems

[0105]

[0106]

[0107] From the data in Table 2, it can be seen that compared with Comparative Examples 1 to 4, the high-performance low-density cement slurry system suitable for large temperature difference conditions prepared in Examples 1 to 9 of the present invention still retains high compressive strength after long-term curing, and the degree of strength decay is low. And compared with Comparative Example 1 without adding a hydration process regulator, the strength decay time node of the cement stone formula with the addition of a hydration process regulator is significantly delayed, and the effect is significant. Compared with Comparative Example 2 without adding a crystal transformation inhibitor, the cement stone with the addition of a crystal transformation inhibitor has a lower degree of strength decline after decay, a better anti-decay effect, a fast and relatively high strength increase, and the strength meets the on-site sealing requirements.

[0108] Experimental Example 3: Porosity and permeability test of different cementing material systems

[0109] The cementing material systems of Examples 1 to 9 and Comparative Examples 1 to 4 were used as test objects. The solid components and liquid water components in the cementing materials used for slurry preparation were first weighed and mixed, and then the slurry was prepared according to the standard GB / T 19139-2012 "Test methods for oil well cement". The cement slurry was first placed in a high-temperature and high-pressure thickener and aged for 1 hour at 140°C and 60 MPa to simulate the temperature increase conditions experienced by the cement slurry after entering the wellbore. Thereafter, the porosity and liquid permeability were measured after curing for 7 days, 30 days, and 90 days at 21 MPa, respectively. The experimental results are shown in Table 3.

[0110] Table 3 Compressive strength properties of different cementing material systems

[0111]

[0112]

[0113] From the data in Table 3, it can be seen that the high-performance low-density cement slurry system suitable for large temperature difference conditions prepared in Examples 1 to 9 of the present invention still has a low porosity and liquid permeability after long-term curing, that is, the modified hollow glass microspheres added to the cement paste participate in the hydration reaction, and the product fills the pore space inside the cement paste, and by improving the bonding ability between the cement paste and the surface of the hollow glass microspheres, the cracking and pore expansion inside the cement paste are reduced. Obviously, the modified hollow glass microspheres have a certain inhibitory effect on the pore growth inside the cement paste, and have a positive effect on improving the density inside the cement paste.

[0114] Experimental Example 4: Low-temperature early strength development of different cementing material systems

[0115] The cementing material systems of Examples 1 to 9 and Comparative Examples 1 to 4 were used as test objects. The solid components and liquid water components in the cementing materials used for slurry preparation were first weighed and mixed, and then the slurry was prepared according to the standard GB / T 19139-2012 "Test methods for oil well cement". The slurry was aged at 140°C and 60MPa for 1h, and then the compressive strength was measured after curing at 30°C and 60°C for 24h and 48h, respectively. The experimental results are shown in Tables 4 and 5.

[0116] Table 4 Low temperature early strength properties of different cementing material systems (30℃)

[0117]

[0118]

[0119] Table 5 Low temperature early strength properties of different cementing material systems (45℃)

[0120]

[0121] From the data in Table 4, it can be seen that the high-performance low-density cement slurry systems suitable for large temperature difference conditions prepared in Examples 1 to 9 of the present invention have a strength greater than 5.1 MPa at 30°C and 24 hours, meeting the requirements of early strength cementing strength on site. Compared with the test results of Comparative Examples 1 to 4, the cement slurry formulas of Examples 1 to 9 have a faster and relatively higher strength increase under medium and low temperature conditions, while the low-density cement slurry of Comparative Examples 1 to 3 with the same retarder added has a slow strength increase under low temperature conditions, but is still better than Comparative Example 4 without the retarder added.

[0122] In summary, the high-performance low-density cement slurry system suitable for large temperature difference conditions provided by the present invention can meet the requirements of long sealing section mining cementing, especially improve the strength development rate of the system under medium and low temperature conditions, promote the rapid development of the strength of hydration products, and ensure that the long-term strength of the hydration products does not decline under high temperature conditions. It has important practical significance for the safe and efficient operation of cementing in long sealing sections and has good application prospects.

[0123] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A high-performance low-density cement slurry system composition and application suitable for a wide temperature range, characterized in that: The composition comprises the following components by weight: 100 parts of oil well G grade cement, 20-28 parts of modified hollow glass microspheres, 3-15 parts of hydration process regulator, 5-10 parts of crystal transformation inhibitor, 1-2 parts of drag reducer, 3-6 parts of fluid loss reducer, 3-4 parts of retarder, 0.2-1.0 parts of defoamer and 44-54 parts of water; The high-performance low-density cement slurry system suitable for a wide temperature range specifically refers to adding three key additives, namely, modified hollow glass microspheres, hydration process regulators, and crystal transformation inhibitors, to conventional oil well cement to improve the overall performance of the cement slurry; wherein, the modified hollow glass microspheres reduce the density of the cement slurry while participating in the hydration reaction to increase the internal density of the cement stone, and improve the early mechanical strength and development rate; the hydration process regulator induces a secondary hydration reaction in the middle and late stages of cement hydration, thereby promoting the further consumption of the loosely structured lamellar deposition product Ca(OH)2 in the cement, and Transformed into stable hydration products, prolonging the strength increase period of cement paste; the crystal transformation inhibitor inhibits the coarsening structural transformation of hydrated calcium silicate in cement paste, reduces the generation of loose structure low calcium-silicon ratio products, and reduces the strength reduction caused by long-term hydration; the above three admixtures play a synergistic role to form a high-friction interlocking structure between cement paste and hollow glass microspheres, and by increasing the generation of high-strength hydration products and the density of cement structure, while ensuring the rapid development of early strength of cement paste, the strength increase period is extended, and the mechanical strength decline of cement paste after long-term evolution is greatly reduced; The modified hollow glass microspheres are prepared by depositing highly active nano-silicon dioxide on the surface of low-reactive hollow glass microspheres. The highly active nano-silicon dioxide on the surface reacts with calcium hydroxide in cement to form a volcanic ash, thereby increasing the content of high-strength hydrated calcium silicate. The nano-silicon dioxide deposited on the surface enhances the surface roughness of the hollow glass microspheres, thereby further enhancing the bonding strength between the cement and the hollow glass microspheres, reducing the cracking and crack expansion between the cement stone and the hollow glass microspheres, and enhancing the mechanical strength of the cement stone from the perspective of microscopic physical structure. The specific composition of the modified hollow glass microspheres is recorded in parts by weight as follows: 30 to 45 parts of hollow glass microspheres, 1,2-tetraethyl orthosilicate, and 1,2-tetraethyl orthosilicate. The invention discloses a method for preparing a modified hollow glass microsphere, comprising: adding 20 parts of tetraethyl orthosilicate and 20 parts of anhydrous ethanol to 60 parts of deionized water, adjusting the pH value to 2.5 with hydrochloric acid, stirring at 300 to 550 r / min until the solution is clear, and then adjusting the pH value to 7.5 with ammonia water to form a silicon dioxide prefabricated liquid, and then placing a plurality of hollow glass microspheres in a high-temperature fluidized bed, wherein the temperature inside the fluidized bed is set to 70 to 80°C, and the gas flow rate inside the fluidized bed is set to 40 to 60 m / s. 3 / h, making the hollow glass microspheres float inside the fluidized bed, and finally gradually spraying the silica prefabricated liquid onto the surface of the hollow glass microspheres at a rate of 10g / mL. After a period of time, the hollow glass microspheres that sink to the bottom of the fluidized bed are collected, cleaned, and dried to obtain modified hollow glass microspheres with a density between 0.58-0.65g / cm 3 , particle size D 90 ≤100μm; The hydration process regulator prolongs the time interval of the strength rise period of cement paste by promoting the secondary hydration reaction in the middle and late stages of the reaction, thereby prolonging the time node of the strength decline. The hydration process regulator is obtained by grinding coal gangue, bauxite, montmorillonite and zirconium oxide into powder and calcining them, and then mixing them evenly according to the weight ratio of 15-25:20-35:25-30:25-30, wherein the particle size of coal gangue is between 40 and 65 μm, the particle size of bauxite is between 20 and 65 μm, the particle size of montmorillonite is between 35 and 75 μm, and the particle size of zirconium oxide is between 30 and 65 μm. The preparation process is to preliminarily crush the coal gangue, bauxite, montmorillonite and zirconium oxide, mix them and perform ball milling, and after the ball milling, calcine the above mixed materials at high temperature, and screen them with a 200-mesh sieve after mixing. The mixed materials are the hydration process regulator, and the main components are alumina, silicon dioxide and zirconium oxide. The crystal transformation inhibitor is a high-calcium mineral material, which reduces the generation of loose structure low calcium-silicon ratio products by inhibiting the coarsening structural transformation of hydrated calcium silicate in cement slurry; the crystal transformation inhibitor is obtained by mixing calcium aluminate, hydrocalumite and spodumene tailings powders after ball milling in a ratio of 20-30:30-45:20-40 by weight, wherein the particle size of calcium aluminate is between 30 and 50 μm, the particle size of hydrocalumite is between 40 and 60 μm, and the particle size of spodumene tailings powder is between 45 and 60 μm.

2. A high-performance low-density cement slurry system suitable for a wide temperature range, characterized in that The fluid loss reducer is obtained by free radical copolymerization of N,N-dimethylacrylamide (NNDMA), 2-acrylamide-2-methylpropanesulfonic acid (AMPS), sodium styrene sulfonate (SSS) and acrylic acid (AA) in a weight ratio of 27-40:24-38:10-16:18-27 in pure water at 50-55°C through a sodium bisulfite-ammonium persulfate initiator system, wherein the reaction pH is 5.5-6.5 and the reaction time is 240-300 minutes.

3. A high-performance low-density cement slurry system suitable for a wide temperature range, characterized in that The retarder is prepared by dissolving itaconic acid (IA), 2-acrylamido-2-methylpropanesulfonic acid (AMPS), N,N-dimethylacrylamide (NNDMA) and a long-chain alkyl quaternary ammonium salt-containing hydrophobic monomer in deionized water in a weight ratio of 6.57-10.51:8.36-9.2:1:0.8-1.21, and adding a persulfate-sodium bisulfite initiator to undergo an oxidation reaction, wherein the reaction pH is 4-6 and the reaction time is 10-12 hours.

4. The high-performance low-density cement slurry system suitable for a wide temperature range according to claim 1, characterized in that: The drag reducer is one of sulfonated aldehyde ketone condensation drag reducers, naphthalene sulfonate drag reducers and polycarboxylic acid drag reducers, or a mixture thereof; the defoamer is one of phosphate defoamers, organosiloxane defoamers, organic polyether defoamers and organosilicon ether defoamers, or a mixture thereof; the oil well cement is G-grade oil well cement or H-grade oil well cement; and the water is fresh water or low-mineralized water.

Citation Information

Patent Citations

  • A high-temperature-difference, low-thermal-conductivity cement slurry suitable for cementing long sealing sections.

    CN112094091B

  • Ultralow-density cement paste system and ultralow-density cement paste additive

    CN116023071A

  • Low-thermal-conductivity additive for deepwater shallow well cementation as well as preparation method and application of low-thermal-conductivity additive

    CN117025188A

  • Preparation method and application of modified fly ash floating bead and ultra-high performance concrete

    CN118388161A

  • High-temperature large-temperature-difference early-strength low-density well cementation cement slurry and preparation method thereof

    CN119100704A